Analysis of Mathematics Learning Outcomes for SMP Negeri 3 Kisaran Students on One Variable Linear Equation Systems (SPLSV) Material Using Learning Models Problem Based Learning (Pbl) - Wulandari, Putri; Rahmadani, Elfira; Masithoh, Ety (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research aims to analyze the mathematics learning outcomes of students at SMP Negeri 3 Kisaran on the One Variable Linear Equation System (SPLSV) material using the Problem Based Learning (PBL) learning model. The method used in this research is descriptive qualitative. This research was conducted at SMP Negeri 3 Kisaran in class VII-2, totaling 32 students. Based on the research results, it was found that there were 2 students with very high criteria with a percentage of 6.25%, 11 people with high criteria 34.375%, 17 people with medium criteria with a percentage of 53.125%, 2 people with low criteria and an average score of students obtained in mathematics learning was 20.28 with a percentage of 81%, this value is said to be included in the good category. This means that the mathematics learning carried out by class VII-2 students at SMP Negeri 3 Kisaran is considered good.